Modern library services in digital era - Narnaware, Sunil (New Delhi D. P. S. Publishing House, 2022)
The Digital library plays an important role in promoting the use of information. Digital libraries give solutions to main challenges to traditional libraries such as storage. Many resources are now available in digital format, from reference titles to e-books, they are managing via integrated library systems, digital libraries and accessed using wen based online public access catalogues, discovery tools and library portals.
Keywords: Modern Library; Digital Library